A DESCRIPTIVE STUDY TO ASSESS THE PERCEPTION ON DEATH AND DYING AMONG NURSING STUDENTS IN SELECTED COLLEGES OF NURSING IN UDUPI DISTRICT, KARNATAKA STATE - Jawahar, Preethy; Alex, Soumya; George, Anice (Journal of Health and Allied Sciences NU, 2013)
Objective: The objectives of the study were assess nursing students perception on death and dying and to identify the perception on death and dying among nursing students of different levels.Materials and Methods: A descriptive survey design was used. Data were collected from 210 nursing students in selected Colleges of Nursing in Udupi district, Karnataka state by using semi structured questionnaire.Result: Thoughts: while caring dying patients and their families, 66.6% perceived thoughts regarding the physical, emotional, spiritual care given to patients who were dying and 77.6% regarding their family or friends. 57.1% perceived thoughts regarding their sufferings, 88% perceived thoughts about a realization that death is a part of life, 29.5% perceived thoughts about the survival and 42.8% perceived that being able to care for dying patients as a privilege and it is an opportunity to work with those who are going through the dying process.Feelings: 40.5% nursing students had physiological symptoms like nausea, muscle tension, headache, 53.8% had fear, 68.5% developed compassion, 86.6% had sadness and 46.2% developed anxiety while caring for dying patients and their families.Challenges: 67.1% of nursing students unaware about how to communicate with unresponsive patient, 61.9% expressed they had language barrier and 71.4% developed problems related to severe emotions while caring dying patients and their families.Conclusion: There is a great need to educate students about death and dying, cultural competence, communication skills and coping with emotional stress.
Keywords: perception; death and dying; feelings; thoughts; challenges